(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
According to Marvin Carlson, performance is an “essentially contested concept”, i.e. a concept which has disagreement about its essence built into the concept itself. An essentially contested concept implies recognition of rival uses of it, as not only logically possibile and humanly “likely”, but as of permanent critical value to one’s own use or interpretation. This feature is even more important nowadays, when performance is not limited to theatre and performance art but emerges (along with its theoretical partner, performativity) as central metaphor and critical tool for a wide variety of studies, covering almost every aspect of human activity. Following Carlson’s as well as Schechner’s and Jon McKenzie’s stimulating ideas, the article asks a bundle of questions. What do we exactly mean by performance? What defines, in particular, performing arts (theatre, music and dance) compared to arts that could not be properly called performative? And what one should exactly intend for performativity in the arts? According to McKenzie, in today’s world performance can refer to experimental art, productivity in the workplace, and functionality of technological systems. My aim is to argue that performing arts (in the field of cultural performances) work as a ‘countervailing thrust’ (in McLuhan’s words) against efficiency as operating principle in organizational and technological performance.